2015
DOI: 10.1016/j.cgh.2014.08.028
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Obstructive Sleep Apnea on Sleep Quality, Cognition, and Driving Performance in Patients With Cirrhosis

Abstract: Background & Aims: In patients with cirrhosis, sleep disturbances are assumed to result from hepatic encephalopathy (HE). The effects of obstructive sleep apnea (OSA) on cognition, sleep parameters, or driving in patients with cirrhosis are unclear. Methods: We performed a cross-sectional, prospective study of 118 subjects. Subjects were assigned to 1 of 4 groups: those with OSA and cirrhosis (without HE or ascites, n=34), those with only cirrhosis (n=30), those with only OSA only (n=29), and those without O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 27 publications
0
23
0
Order By: Relevance
“…Indeed, Bajaj et al have observed EDS and poor quality of sleep in compensated cirrhotics compared to healthy controls. 10 Comparison of sleep in cirrhosis with prior HE vs without prior HE has also highlighted a further deterioration of sleep quality, with more non-restorative sleep. 11 Etiology of cirrhosis does not influence the occurrence/the clinical picture of sleep disturbances that have been observed both in series of patients affected exclusively or mainly by hepatitis C 2 , 10 , 11 , 12 and in series including a majority of alcoholic cirrhosis.…”
Section: Clinical Manifestations Of Sleep Disturbances In Liver Cirrhmentioning
confidence: 99%
“…Indeed, Bajaj et al have observed EDS and poor quality of sleep in compensated cirrhotics compared to healthy controls. 10 Comparison of sleep in cirrhosis with prior HE vs without prior HE has also highlighted a further deterioration of sleep quality, with more non-restorative sleep. 11 Etiology of cirrhosis does not influence the occurrence/the clinical picture of sleep disturbances that have been observed both in series of patients affected exclusively or mainly by hepatitis C 2 , 10 , 11 , 12 and in series including a majority of alcoholic cirrhosis.…”
Section: Clinical Manifestations Of Sleep Disturbances In Liver Cirrhmentioning
confidence: 99%
“…OSA is associated with elevated alanine aminotransferase levels and a trend toward histologic evidence of progressive liver disease [ 22 ]. A small sample size study of 17 patients showed improvement in executive functions after continuous positive airway pressure (CPAP) treatment of OSA, which was in turn an independent predictor of concomitant liver cirrhosis [ 23 ]. An interesting study found that chronic intermittent hypoxia in mice with induced obesity is associated with liver fibrosis due to activation of pro-inflammatory pathways of liver fibrosis [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…These findings point toward the importance of assessing daily function concerns at each clinical visit, both physical and mental, along with communicating the plan of care with patients and their family members. Examples of this would be addressing nutritional status to improve sarcopenia and muscle strength [36], and sleep disturbances which can be a sign of impending HE [37] or undiagnosed obstructive sleep apnea [38].…”
Section: Discussionmentioning
confidence: 99%